Experimental performance characterisation of a Hybrid Photovoltaic/Solar Thermal Façade module compared to a flat Integrated Collector Storage Solar Water Heater module. (July 2019) - Smyth, M.; Pugsley, A.; Hanna, G.; Zacharopoulos, A.; Mondol, J.; Besheer, A.; Savvides, A.
Abstract: A modular Hybrid Photovoltaic/Solar Thermal (HyPV/T) Façade technology that utilizes Integrated Collector Storage (ICS) solar technology, providing cost effective solar PV and thermal energy collection for direct use in the building, whilst providing significant thermal insulation has been developed and evaluated experimentally at Ulster University. The HyPV/T system, based upon a patented ICS solar thermal diode concept and shaped into a flat modular profile incorporating PV cells/module can provide space heating, domestic water heating and power generation. The complete system is designed to be compatible with traditional façade structures and fenestration framing arrangements, facilitating direct integration into new and retrofit building applications. The experimental performance of HyPV/T unit has been determined and compared with a flat Integrated Collector Storage Solar Water Heater (ICSSWH) under constant indoor solar simulated conditions. The daily thermal collection efficiencies for the 'traditional' flat ICSSWH units performed better than the unglazed HyPV/T, by 5–10%. However, when the additional electrical power produced by the HyPV/T is included, the overall system collection efficiencies are more equal. The heat retention performance shows that's the unglazed (bare) ICS unit had a retention efficiency of 8.3% whilst the ICS unit with a single transparent cover was 23.6% and double glazed unit was 28%. The HyPV/T heat retention efficiencies were approximately 65% over the same cool-down period. Highlights: Hybrid Photovoltaic/Solar Thermal (HyPV/T) Façade technology. Novel thermal diode operation. Experimental evaluation via a solar simulation test facility. Unglazed HyPV/T thermal and PV efficiencies under zero temperature rise conditions of 56% and 9%, respectively. HyPV/T heat retention efficiencies of 65%.